Evidence of bovine viral diarrhea virus in buffaloes (Bubalus bubalis) in Nineveh province - Qaes T. Alsarhan; Fanar A. Isihak; Sadam D. Hasan; Osama Z. Abdulla; Wisam S. Hassan (Iraqi Journal of Veterinary Sciences)
Investigating the sources of Pestivirus, family Flaviviridae, and bovine viral diarrhea virus (BVDV) infections is important in the epidemiology and control efficacy of this disease in large and small ruminants. This work is a preliminary attempt to investigate the prevalence of BVDV in buffalo by conducting a reverse transcriptase polymerase chain reaction in Nineveh province, Iraq. From November 2024 to the end of January 2025, a total of 158 blood samples were collected from buffaloes in 7 farms in various areas of Nineveh province, and from both sexes, different management, sole and interspecies rear, and no vaccination background against the disease. The molecular outcome objective 5’ UTR gene region revealed a 7.59% total prevalence of BVDV, with a significantly higher prevalence of BVDV in buffaloes aged more than 5 years. Further, no statistical variability among buffaloes' sex, management, and study areas. Six procuring sequences in the current work are bookmarked in the GenBank database under identity numbers. Furthermore, the local sequences referenced were similar to those of Iran, Iraq, Mexico, China, and the USA (96.07%-100% identity). In conclusion, the bovine viral diarrhea virus was recorded in this work for the first time in Nineveh province, although the disease was reported earlier in cattle and sheep. Attention should be given to the role of buffalo in transmission and maintaining the virus. Hence, precise detection and differentiation of Pestivirus are crucial requirements for the elimination and evacuation efforts of BVDV in the animal population.